Sarcopenia and falls in community-dwelling elderly subjects in Japan: Defining sarcopenia according to criteria of the European Working Group on Sarcopenia in Older People - Tanimoto, Yoshimi; Watanabe, Misuzu; Sun, Wei; Sugiura, Yumiko; Hayashida, Itsushi; Kusabiraki, Toshiyuki; Tamaki, Junko (Archives of gerontology and geriatrics, 2014)
This study assessed the association between sarcopenia (using the definition of the European Working Group on Sarcopenia in Older People) and fall in the past year among community-dwelling Japanese elderly. Subjects were 1110 community-dwelling Japanese aged 65 or older. We used bioelectrical impedance analysis (BIA) to measure muscle mass, grip strength to measure muscle strength, and usual walking speed to measure physical performance in a baseline study. “Sarcopenia” was characterized by low muscle mass and low muscle strength or low physical performance. “Presarcopenia” was characterized only by low muscle mass. Subjects who did not have any of these deficiencies were classified as “normal.” We then administered a questionnaire assessing age, sex, household status, chronic illness, lifestyle-related habits, and fall. This study showed the prevalence of fall was 16.9% and 21.3% in men and women, respectively, while that of sarcopenia was 13.4% and 14.9% in men and women, respectively. In men and women, the prevalence of sarcopenia was higher among those who had fallen. A logistic regression analysis using age, body fat, current drinker status, and physical inactivity for men, and age, body fat, smoking, and diabetes for women as covariate variables revealed that sarcopenia was significantly associated with a history of fall. The odds ratio for fall in the sarcopenia group relative to the normal group was 4.42 (95%CI 2.08–9.39) in men and 2.34 (95%CI 1.39–3.94) in women. This study revealed sarcopenia to be associated with falling in elderly Japanese. Sarcopenia prevention interventions may help prevent falls among elderly individuals.